Comparison of Plant Health Aspect In Green Open Spaces of Alun-Alun Kebumen and Alun-Alun Karanganyar, Kebumen, Central Java - Mustika Dewi, Herfiana Anggun; Nasrullah, Nizar; Sulistyantara, Bambang (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Alun-alun Kebumen and Alun-alun Karanganyar are green open spaces located in Kebumen, Central Java. Trees are one component of green open space that has various benefits. The physical condition of the trees is something that needs to be considered in a public green open space so that the trees remain in healthy condition and can grow normally. Study of physical damage of plant at the Alun-alun was raised as a topic of research activity to determine the physical condition of the plants in the Alun-alun in Kebumen Regency. The purpose of this study is to identify the damage of plants and the factors that cause the damage, analyzing the level of gap in plant maintenance had been implemented, and compiling recommendations for plant maintenance in Alun-alun Kebumen and Alun-alun Karanganyar. This plant damage research have been conducted using the FHM (Forest Health Monitoring) method and the USDA Forest Service damage index. Alun-alun Kebumen has an area of 3,9 ha and located in the center of the district, has 16 species of trees, 18 species of shrubs, and 2 species of grass. The tree population in Alun-alun Kebumen is 252 trees. Alun-alun Karanganyar has an area of 3,2 ha and located in a sub-district which is 14 km from the district center. It has 18 species of trees, 15 species of shrubs, and 1 species of grass. The tree population in Alun-alun Karanganyar is 262 trees. The results of this research is that Alun-alun Kebumen had more physical damage of plants with 380 cases from total 252 trees, while Alun-alun Karanganyar had 319 cases from total 262 trees. Damage of trees can be caused by a lack or excess of nutrients, pests or disease. The gap value of plant maintenance in Alun-alun Karanganyar is greater than Alun-alun Kebumen. Handling physical damage of trees is carried out by carrying out routine maintenance combined with chemical treatment in the form of applying pesticides according to the level of tree damage. This research is the initial stage of mitigating fallen trees. Developments that can be implemented after this research are designing green open space for public squares by selecting tree species that have been evaluated for their vulnerability and whose health is monitored regularly